Economies in Transition : Conception, Status and Prospects. - Young, Allan (World Scientific Publishing Company, 2002)
To date, the record of economic transition has decidedly been mixed. The worldwide political climate is still in favor of economic reform and the process continues to have considerable momentum. On the other hand, this process now faces a number of formidable obstacles. There appears to be general agreement that in many countries the promise of a better standard of living which economic transition offers to the mass of the citizenry has failed to produce the rapid and dramatic results hoped for. There is an increasing conflict of interest between multinational firms and the national business c.